Seed borne fungi of Brassica chinensis L. and Brassica rapa L. and their pathogenic importance - Kanapathipillai, Vijaya S.; Hashim, Zainab (Ministry of Agriculture, 1981)
In using the filter paper and agar plate procedures, a total of 35 species of fungi, namely, Alternaria brassicae, Aspergillus aculeatus, Acflavus, A. ochraceous, A. terreus, Botryodiplodia theobromae . Choanephora curcurbitarum, Circinella, sp., Cladosporium sphaerosporum, Colletotrichum sp., Cylindocladium sp., Curvularia lunata. C. pallescens, C. oryzae, Diaporthe sp., Erysiphe sp., Fusarium equiseti, F. fusaroides, F. oxysparum, F. moniliforme var subglutinans, Helminthosporium sp., Macrophomina phaseolina, Nigrospora orvzae, Paccilornyces sp., Penicillium nigricans, P. nototum, P. rugulosum, P. wortmanii, Peronospora sp., Pest alotia sp., Phaetricoconis sp .. Phomu linguni. Pythium sp .. Rhizopus stolonifer and Syncephalastruni racemosum were found to be present on seeds of Brassica chinensis and B. rapa. Both Malt extract agar and Potato Dextrose agar gave more infection counts of seeds than filter paper. Surface disinfection with mercuric chloride eliminated contaminants like Aspergillus spp., Penicillium sp., and some mucuraceous fungi, but did not affect germination. Inclusion of sodium chloride in media, allowed growth of osmophilic fungi and did reduce germination of seeds. Soil inoculation tests on emerging seedlings using nine selected isolates indicated, that all fungal isolates tested were pathogenic to seeds and seedlings of Brassica spp. with Brassica chinensis being more susceptible than B. rapa. Macrophomina phaseolina is reported as a pathogen of Brassica spp. for the first time.